Bermain Buku Pop-Up sebagai Terapi Gangguan Mental Emosional Pasca Bencana Tsunami - Sulastri, Sulastri; Rohayati, Rohayati; Febriaty, Sary (Poltekkes Kemenkes Tanjung Karang, 2021)
Traumatic experiences can trigger mental-emotional problems in children, especially in disaster conditions. The purpose of this study is to describe mental and emotional problems in children in South Lampung after the Sunda Strait tsunami natural disaster after being given playing therapy with pop-up books. This study uses a quantitative design with quasi-experimental treatment. The population in this study were preschool and school-age children affected by the Sunda Strait tsunami who lived in temporary village shelters in three villages namely Way Muli Timur, Way Muli Barat, and Kunjir as many as 93 children. The mental-emotional state of the child will be measured before and after therapy. Data collection using the Strength Difficulties Questionnaire questionnaire. The test was conducted using the dependent t-test. The results of data analysis showed that in general the level of strength and difficulty of children was abnormally susceptible (63,4%) at the beginning of the measurement and increased towards normal, in other words, there was an effect of playing therapy with pop-up books on the child's emotional mentality. The results of the bivariate test showed that there was an effect of pop-up books play therapy on children's mental-emotional problems (p-value 0,002). It is recommended that play therapy be combined with other therapies, including consistently to reinforce for children from those closest to them, such as nuclear family and other children's closest people.